Challenges and Strategies of the BPK in Improving the Quality of Regional Government Financial Accountability in the Autonomy Era: Study of the Role of Digital Technology and Public Transparency - Dito Aditia Darma; Reni Vadia; Reza Safrianto (International Journal of Management, Economic and Accounting, 2025)
This study examines the challenges and strategies of the Audit Board of Indonesia (BPK) in improvingquality of local government financial accountability in the era of autonomy, with a focus on the role of digital technology and public transparency. In the context of fiscal decentralization, local financial management faces increasing complexity, causing various problems in accountability and transparency. Through a qualitative approach with a case study method in several local governments in Indonesia, this study identifies the main challenges faced by the BPK, such as limited human resources, inadequate technological infrastructure, and resistance to change. The BPK's strategy in utilizing digital technology such as the implementation of a data-based audit system, a public transparency platform, and increasing digital collaboration with stakeholders has had a significant impact on improving local financial accountability. The results of the study indicate that the integration of digital technology and increasing public transparency play an important role in overcoming structural and cultural barriers in local financial supervision.